Surface modification of carbon fiber with imidazolium ionic liquids. Issue 8 (3rd August 2022) - Ghafoor, Bilal; Schrekker, Henri Stephan; Morais, Jonder; Amico, Sandro Campos
ABSTRACT: Carbon fiber composites are high-performance materials commonly used in advanced applications and their performance is highly dependent on the fiber-matrix interfacial interaction. The non-polar carbon fiber surface may be modified via different techniques to improve adhesion with the polymer matrix. In this work, non-covalent surface modification of carbon fiber has been carried out using two different imidazolium ionic liquids, 1- n -butyl-3-methyl imidazolium bis(trifluoromethylsulfonyl) imide (hydrophobic) and 1- n -butyl-3-methylimidazolium chloride (hydrophilic). The treatment was performed by immersing the fiber into 10 wt. % methanolic ionic liquid solution for 10 min. Treated fibers were characterized using Fourier-transform infrared spectroscopy, Raman spectroscopy and X-ray photoelectron spectroscopy confirmed the presence of ionic liquid on the carbon fiber surface. Surface morphology of treated fibers analyzed by scanning electron microscopy showed ionic liquid moieties. Wettability of the treated carbon fiber with epoxy resin significantly increased, with a decrease in contact angle greater than 15°. Interfacial shear strength between the modified carbon fiber and epoxy increased up to 56.5% with respect to the unsized carbon fiber, being comparable with epoxy-sized fibers. Thus, the proposed surface modification has the potential to improve the interfacial performance of carbon fiber polymer composites. Graphical Abstract: uf0001